(untitled) (Nigerian Journal of Physiological Sciences, 2025)
The study aimed at elucidating the potency of aqueous extract of Talinum triangulare on the hippocampal neurons, astrocytes as well as assessing short term memory of scopolamine-induced Alzheimer’s type rats. Fifty-four Wistar rats (180-200g) were used for the study; thirty experimental rats were randomly grouped into five, each containing six rats designated A, B, C, D and E while twenty-four rats were used to establish 50% lethal dose (LD50). Alzheimer’s type cognitive dysfunction was intraperitoneally (ip) induced with scopolamine hydrobromide (1mg/kg, ip) for seven days in groups B-E prior to the oral administration of the aqueous extract (875 and 1750mg/kg) and donepezil (1mg/kg), followed by the novel object recognition test, histological and GFAP staining processes. Results revealed atrophied pyramidal cells, hyperchromatic, numerous glial cells with pale cytoplasmic inclusions and astrogliosis in groups B, C, and E while group D showed ameliorative potentials compared to group A. Also, short term memory was significantly higher in group D compared to groups B, C and E. In conclusion, aqueous extract of Talinium triangulare leaves reduced the potentials of scopolamine hydrobromide by restoring abnormal neurons, hence, enhancing cognitive memory in the rats used in the present study.